PENGARUH KEPUASAN KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA LPD DESA PAKRAMAN DUKUH, KARANGASEM - Putri Anggreni; I Kadek Sugiantara (Forum Manajemen STIMI Handayani Denpasar, 2021)
The work performance of LPD employees in Dukuh Village, Sidemen District, Karangasem Regency has decreased, marked by a fairly high level of absenteeism every month. This study aims to determine the effect of workload on employee performance, the effect of workload on employee performance, and the effect of job satisfaction and workload on employee performance. The population in this study were 21 employees of the Village Credit Institution (LPD) Pakraman Dukuh Village, Sidemen District, Karangasem Regency. Hypothesis testing using multiple linear regression testing, F-test, and testing the coefficient of determination (R2). The results of research on multiple linear regression analysis show that the workload variable has a positive and significant effect on employee performance and the workload variable has a positive and significant effect on employee performance. Through testing the coefficient of determination (Adjusted R Square), a value of 0.438 or 43.8% is obtained, meaning that employee performance is influenced by job satisfaction and workload by 43.8%, while the remaining 56.2% is influenced by other variables. Company leaders should pay attention to aspects that can increase employee job satisfaction such as satisfaction with the salary received by employees, support from colleagues who support each other, and leaders provide motivation and attention to employees.